Determinants of Costumer’s to Use Islamic Bank: The Case of Muhammadiyah in Region Yogyakarta - Rofiul Wahyudi; Almira Rosa Bella Almira (Social Science Studies, 2022)
This study examines the effect of personal, product, social, and promotion factors on Muhammadiyah residents using Islamic banking at the BSI Yogyakarta Branch. This research uses quantitative research methods with associative research types. The data sources used were primary and secondary data sources. Primary data were obtained through a questionnaire (questionnaire) distributed to Muhammadiyah residents, while secondary data sources were obtained through references. The results showed that Personal Factors, Social Factors, Product Factors, and Promotional Factors partially and simultaneously had a positive and significant effect on the decision of Muhammadiyah residents to use Islamic banks.